The impact of antibiotic use on outcomes of relapsed/refractory multiple myeloma patients treated with CAR-T therapy - Yin, Lingling; Lv, Bin; Ge, Jiao; Qi, Yuekun; Xia, Jieyun; Ma, Sha; Wang, Ying; Liu, Yang; Zhou, Dian; Cao, Jiang; Yan, Zhiling; Qi, Kunming; et al. (Frontiers in Immunology, 2025)
BackgroundIn recent years, chimeric antigen receptor (CAR)-T cell therapy has achieved tremendous efficacy in relapsed/refractory multiple myeloma (R/R MM). However, the impact of antibiotic (ATB) use on R/R MM patients treated with CAR-T is still not known. The aim of our study was to analyse the influence of ATB on the clinical outcomes of R/R MM patients treated with CAR-T cells.MethodsIn this retrospective study, 199 patients with R/R MM who received CAR-T cells between January 2018 and December 2023 were evaluated from two hospitals in China. They were stratified into ATB-group and No ATB-group according to whether ATB was administered in the 4 weeks before therapy. We mainly analyzed the efficacy, survival outcomes and cytotoxicity of CAR-T cell therapy in two groups of patients.ResultIn the ATB group (90 patients), the overall response rate (ORR) was 70% comparable to the No ATB group (109 patients: ORR, 81.7%; P = 0.054). The complete response rate (CRR) was 40%, which was significantly lower compared with No ATB group (CRR, 57.8%; P = 0.012). The median progression-free survival (PFS) was 6.7 months while the median overall survival (OS) was 21.9 months for the ATB group. The median PFS and OS for the No ATB group were 13.9 months and 36.1 months. There were significant differences in PFS (P = 0.007) and OS (P = 0.004) between the evaluated groups. Nonetheless, multivariate analysis found ATB use did not reduce the CRR (odds ratio [OR], 0.947; 95% confidence interval [CI], 0.251 to 3.565, P = 0.936). Besides, administration of ATB did not affect the PFS (hazard ratio [HR], 0.634; 95% CI, 0.28 to 1.436, P = 0.275) and OS (HR, 2.259; 95% CI, 0.755 to 6.762, P = 0.145) in R/R MM patients treated with CAR-T cells. Additionally, both groups of patients had similar incidences of cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS).ConclusionOur results point to a detrimental effect of ATB on treatment outcomes to CAR-T cell therapy. However, the use of ATB is not associated with the incidence of CRS or ICANS.